(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Diri KH, Kedoneojo AT. 2024. Evaluating the impact of poultry manure variants and swine manure on soil chemical properties and growth of maize (Zea mays). Asian J Agric 8: 1-9. A greenhouse experiment was conducted at the Niger Delta University Teaching and Research Farm, Nigeria, to assess the impact of various organic manure sources on soil chemical properties and maize growth. The treatments included three variants of poultry manure (broiler manure (PB), layers poultry manure (PL), point of lay poultry manure (POL)), swine manure (SW), and combined treatments of swine manure with each poultry manure variant. Three application rates (0 (L0), 10 (L1), and 20t/ha (L2)) were employed for each treatment. The experiment followed a 7×3×3 factorial fitted into a randomized complete block design, with treatments replicated thrice; the test crop used was maize (Zea mays L.). Soil samples were collected before and after the experiment to evaluate the effect of each organic treatment on soil chemical properties. Statistical Analysis of Variance (ANOVA) was conducted on the collected soil and plant data, with mean separation performed using Tukey’s t-test. The results showed significant differences (p < 0.05) between the experimental and control treatments, with notable effects on soil chemical properties. In soils, the SWPL (L2) treatment presented the highest average values ??for pH (6.06), organic matter (2.95%), calcium (0.96 cmol/kg), magnesium (0.77 cmol/kg), potassium (0.54 cmol/kg), base saturation (63%), and effective cation exchange capacity (3.68 cmol/kg). The highest mean value for total soil nitrogen corresponded to the PL treatment (L2). Plant parameters also exhibited significant differences (p <0.05) compared to the control, with the most pronounced effects observed in the PL (L2) and SWPL (L2) treatments. These findings suggest that utilizing poultry manure from layers, combined with swine manure, positively influences soil quality, productivity, and maize growth. Thus, maximizing the use of these organic manure sources as alternatives for fertilizer application is recommended.